Is body mass index as a predictor of hepatic steatosis in living liver donors? - Bozkurt, Birkan; Adalı, Gupse; Dayangaç, Murat; Yüzer, Yıldıray; Tokat, Yaman (Lippincott Williams & Wilkins, 2018)
[Abstract Not Available]
Joint International Congress of ILTS, ELITA and LICAGE -- MAY 23-26, 2018 -- Lisbon, PORTUGAL
WOS: 000436897700459